2023
DOI: 10.1029/2023gl103331
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Bend‐Faulting and Mantle Hydration at the Marianas Trench From Seismic Anisotropy

Abstract: Subduction zones are a locus of material transfer between the surface and the solid Earth and play a key role in global cycling of water and other volatiles over geologic time. Balancing the global water budget requires knowing the amount of water recycled to the mantle by subduction, but current estimates span an order of magnitude (Hacker, 2008;Rupke, 2004;Schmidt & Poli, 2003;van Keken et al., 2011). The largest source of uncertainty for subduction zone water fluxes is the amount of water carried in the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
(97 reference statements)
0
8
0
Order By: Relevance
“…Cai et al (2018) attributed part of the large VS reduction in the Mariana outer-rise mantle to water in cracks and joints. Mark et al (2023) found evidence from seismic anisotropy for water in crack-like pores in the upper 1 km of the Mariana outer rise mantle using active-source data. If the water in crack-like porosity exists in the mantle, the percent serpentinization determined by VS values and the VP/VS ratios will be overestimated.…”
Section: Comparison With Previous Active Source Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Cai et al (2018) attributed part of the large VS reduction in the Mariana outer-rise mantle to water in cracks and joints. Mark et al (2023) found evidence from seismic anisotropy for water in crack-like pores in the upper 1 km of the Mariana outer rise mantle using active-source data. If the water in crack-like porosity exists in the mantle, the percent serpentinization determined by VS values and the VP/VS ratios will be overestimated.…”
Section: Comparison With Previous Active Source Resultsmentioning
confidence: 97%
“…The actual situation may be more complex, as the serpentinization may be localized in narrow regions surrounding discrete faults (Hatakeyama et al, 2017). In this case, there will be frequency-dependent wave propagation through the mantle at the frequencies used in active source studies (Miller & Lizarralde, 2016;Miller et al, 2021;Mark et al, 2023). Estimates of serpentinization taking this effect into account generally result in smaller percentages of serpentinization, but require analysis of azimuthal anisotropy, which is not available in this case.…”
Section: Comparison With Previous Active Source Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The velocities decrease toward the trench and show significant along‐strike variations. Low‐velocity zones at the top of the incoming plate mantle have been observed at many other subduction zones and are generally attributed to the serpentinization of mantle peridotite (Cai et al., 2018; Ivandic et al., 2008; Mark et al., 2023; Shillington et al., 2015; Van Avendonk et al., 2011) and/or to the effects of water in plate‐bending faults (Korenaga, 2017; Miller & Lizarralde, 2016). The Shumagin segment shows a distinct low‐velocity zone (∼3.65 km s −1 ) at the top of the incoming plate mantle, suggesting strong hydration if the velocity reduction is due to serpentinization.…”
Section: Discussionmentioning
confidence: 99%